Looking for Information-Literate Thinking in Undergraduate Subject Searching - Graham, Rumi Y. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
To what extent do upper-level, academically outstanding undergraduates employ the kind of higher-order information literate thinking during subject searching commonly associated with search and domain experts? This paper reports on a multiple case study exploration of this question involving eight students and their genuine academic subject searches over a school year. Dans quelle mesure les étudiants de premier cycle universitaire aux meilleurs résultats académiques emploient-ils des techniques de littératie de haut niveau communément trouvées chez les experts lors de recherches par sujet? Cette communication présente les résultats de huit études de cas menées auprès d’étudiants suivis pendant leur cheminement scolaire au cours d’une année.